Temperature control of open-cathode PEM fuel cells. Issue 1 (July 2017) - Strahl, Stephan; Costa-Castelló, Ramon
Abstract: Proper temperature control of Proton Exchange Membrane (PEM) Fuel Cells is a crucial factor for optimizing fuel cell performance. A robust temperature controller is required for optimal water management of PEM fuel cells. This paper describes a model-based characterization of the equilibrium points of an open-cathode fuel cell system as the baseline for proper controller design, highlighting the relation between fuel cell temperature, humidification and performance. Phase plane analysis of the nonlinear model versus a linearized model around different points of operation shows the potential of approximating the nonlinear system behavior with a linear model. The methodology for the system analysis presented in this paper finally serves for the development of control schemes using robust control techniques. The designed controller is validated in simulation with the nonlinear plant model.